Contemporary views on architecture and representations in phonology [ - Cairns, Charles E.; Raimy, Eric (Current studies in linguistics, 2009)
Leading phonologists discuss contemporary work on the topics of metrical theory, feature theory, syllable theory, and the relation among grammatical modules